Components and dispersion characteristics of organic and inorganic odorous gases in a large-scale dairy farm. (3rd June 2019) - Guo, Haobo; Hao, Hairui; Zhang, Qiuping; Wang, Juan; Liu, Jianguo
ABSTRACT: The rapid development of large-scale livestock husbandry has caused serious air pollution problems (e.g., The Tuzuoqi demonstration farm belonging to the Yili Group. The farm is located in the suburb of Hohhot City in northern China). In this study, the gases in typical areas of a large-scale dairy farm were sampled and measured for volatile organic compounds (VOCs), hydrogen sulfide, and ammonia concentrations. Fifty-two species of VOCs were identified. The VOCs emitted from the cowshed mainly consisted of halogenated hydrocarbons (16, 960 µg/m 3 ), ketones (15, 700 µg/m 3 ), esters (9889 µg/m 3 ), and sulfur compounds (3677 µg/m 3 ). The VOCs from the oxidation pond were mainly composed of halogenated hydrocarbons (21, 940 µg/m 3 ) and ketones (3589 µg/m 3 ). The VOCs from the solid–liquid separation tank comprised halogenated hydrocarbons (32, 010 µg/m 3 ), ketones (7169 µg/m 3 ), and sulfur compounds (1003 µg/m 3 ). The highest concentrations of ammonia and hydrogen sulfide were obtained from the milking parlor and solid–liquid separation tank, respectively. The ammonia concentration declined gradually due to the superposition of ammonia emitted from the cowshed and milking parlor. Analysis results of the influences of distance and meteorological factors on the dispersion of ammonia and hydrogen sulfide suggested that the dilution factors decreased with increasing distance from the emission source. Within distance ranges of 0–10 and 10–25 m, the concentration dilution factors were positively correlated with wind speed and temperature but negatively correlated with humidity and atmospheric pressure. The results of our work can provide a theoretical basis for the prevention and control of odorous gases in large-scale livestock farms. Implications: Gases in typical areas of a large-scale dairy farm were sampled, and a total of 52 species of VOCs were identified. The highest concentrations of ketones, sulfur compounds, and esters were obtained at the cowshed (15, 700, 3677, and 9889 µg/m 3, respectively). Within the distance ranges of 0–10 and 10–25 m, the concentration dilution factors were positively correlated with wind speed and temperature.